PENINGKATAN HASIL BELAJAR IPS SISWA KELAS IV DENGAN PENDEKATAN INKURI DI SEKOLAH DASAR - Putri, Irma Dewi Riza; Faridas, Faridas; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The problem in this research is the less able teachers to develop the learning approach that can activate the students optimally in the learning process. The purpose of this research is to describe and get information about the improvement of IPS learning result by using Inquiry approach. The subjects of the study were students of class IV, amounting to 20 people. The type of research used is classroom action research. Data were collected using an observation sheet and a table of notes. The result of this research is the increase of the average grade value from 73,5 in cycle I to 83 in cycle II. So it can be concluded in this study is to use inquiry approach in learning IPS can improve student learning outcomes   Keywords: IPS Learning Outcomes, Inquiry Approach